CUSTOMARY VILLAGE-BASED FOREIGN CAPITAL INVESTMENT MANAGEMENT - I Nyoman Agus Prabawa (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract The Economic Policy Package Volume X has been announced by the Government on February 11th, 2016. The concrete step of the policy package is to revise the Presidential Regulation concerning the field of business in investment known as the negative list of investment. Areas of business that are experiencing changes in the negative list of investment include the sector of Tourism and Creative Economy. In Bali, the tourism appeal is built and developed, apart from Government and private, is also managed by the community of customary villages. The existence of customary village-based tourism can attract foreign investors or otherwise require foreign capital which may then be agreed upon in the form of agreement. In addition to globalization, other things that could lead to the possibility of such agreement are the liberalization in the field of investment and tourism. Liberalization arises from various international agreements that have been agreed by the Government, such as one of ASEAN regional liberalization with the ASEAN Economic Community. So, to face that possibility, the Government needs to regulate foreign investment in customary village based tourism with various levels of policy. As a normative legal research, the method used in this study is a legislative approach that is integrated with a conceptual approach. Policy and legislation have variations in relationships based on differences in understanding and application of the use of policy concepts. The policies studied in normative legal research, in addition to legislation also concerning government actions relating to the terms discretion, policy, beleid, and ermessen are reviewed. Keywords: Arrangement, foreign investment, customary village-based tourism